Kinematics of the foot joint in female soccer players during the ball impact phase of kicking - Sakamoto, K.; Geisler, G.; Nakayama, M.; Asai, T. (Procedia Engineering, 2010)
The purpose of this study was to reveal the kinematic interactions that occur in female soccer players during the ball impact phase of kicking. A total of 34 soccer players (17 females and 17 males) performed maximal instep kicks, infront kicks, and inside kicks while the behavior of the ball and kicking foot were captured three dimensionally by two high-speed cameras at 1,000 fps. Statistically significant differences emerged between the male and female players. Specifically, the mean values for ball velocity and foot velocity of the three types of kicks were lower among female players than male players (p<.05). Moreover, the coefficient of restitution of the inside kick was larger for female players than for male players (p<.05).